Social Media Approach to Crisis Communication During the COVID-19 Pandemic: A Case Study of Saudi Arabia - Norizzati Azudi; Rosninawati Hussin; Suria Hani A. Rahman (Taylor's University, 2024)
Indexed by WOS/ Scopus